A dynamic route change mechanism for mobile ad hoc networks. (1st January 2011) - Wu, C.; Kumekawa, K.; Kato, T.
A mobile ad hoc network (MANET) is a self-configuring network of mobile devices connected by wireless links. Frequent topology changes and limited bandwidth make communication in MANETs particularly challenging. We present a MANET routing protocol that can efficiently handle network mobility by a way of preemptively switching to a better route before the current route fails. The protocol uses a distributed Q-learning algorithm to infer network status information and takes in to consideration link stability and bandwidth efficiency while selecting a route. We study the performance of this protocol through simulation and demonstrate its advantages over existing protocols.